L’inter-mythualite : Entrevision - Grigoriu, Brindusa (University of Eloued جامعة الوادي, 2024)
The present article is a contribution to the construction of a concept, inter-mythuality (inter-mythualité), which is achieved in a transdisciplinary perspective. Etymological considerations cannot be limited to a lexical approach, when intercultural communication is concerned, especially in diachronic contexts. Literary grounds support the semantic and pragmatic dimensions of this neological construct, our casestudy being represented by the myth of the Philter in the medieval Romances of Tristan.
Article. Ex Professo. Vol 09. N.01 .University of El oued
Keywords: inter-mythuality; Tristan Romances; myth of love as a Philter; transdisciplinary approach